2017
DOI: 10.1128/jvi.01419-16
|View full text |Cite
|
Sign up to set email alerts
|

Restarting Lytic Gene Transcription at the Onset of Herpes Simplex Virus Reactivation

Abstract: Herpes simplex virus (HSV) establishes a latent reservoir in neurons of human peripheral nerves. In this quiescent state, the viral genome persists as a circular, histone-associated episome, and transcription of viral lytic cycle genes is largely suppressed through epigenetic processes. Periodically, latent virus undergoes reactivation whereby lytic genes are activated and viral replication occurs. In this Gem, we review recent evidence that mechanisms governing the initial transcription of lytic genes are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 39 publications
2
77
0
Order By: Relevance
“…Two discrete waves of viral productive cycle gene transcription, termed Phases I and II, were identified in latently-infected cultured neurons following inducible reactivation (Kim et al, 2012). By phosphorylating histone H3 ser10 adjacent to repressive di- or trimethylated H3 lys9, the neuronal JNK stress pathway overrides epigenetic silencing to activate viral promoters in Phase I ( Cliffe et al, 2015 ; Cliffe & Wilson, 2016). The resulting burst of transcription from viral genomes includes all HSV-1 genes irrespective of their kinetic class [ immediate-early (IE), early, leaky-late and true-late ], is independent of protein or DNA synthesis, and proceeds without infectious virus production.…”
Section: Introductionmentioning
confidence: 99%
“…Two discrete waves of viral productive cycle gene transcription, termed Phases I and II, were identified in latently-infected cultured neurons following inducible reactivation (Kim et al, 2012). By phosphorylating histone H3 ser10 adjacent to repressive di- or trimethylated H3 lys9, the neuronal JNK stress pathway overrides epigenetic silencing to activate viral promoters in Phase I ( Cliffe et al, 2015 ; Cliffe & Wilson, 2016). The resulting burst of transcription from viral genomes includes all HSV-1 genes irrespective of their kinetic class [ immediate-early (IE), early, leaky-late and true-late ], is independent of protein or DNA synthesis, and proceeds without infectious virus production.…”
Section: Introductionmentioning
confidence: 99%
“…These findings presented here could be of general interest as the expression of HSV TK in cancer cells has been recently exploited in strategies for cancer therapy [64]. Moreover, the reactivation of silent HSV copies in nerve cells is a common occurring health risk and the expression of HSV TK is crucial for the reactivation of HSV in human nervous cells [65].…”
mentioning
confidence: 71%
“…As reviewed recently, the process of reactivation likely requires multiple steps (Cliffe and Wilson, 2017; Sawtell and Thompson, 2016a). In primary neuronal culture systems, it has been shown that there is an initial relaxing of the chromatin structure, which likely includes multiple changes that may or may not be accompanied by detectable increases in lytic gene transcription.…”
Section: Triggers Implicated In Hsv Reactivationmentioning
confidence: 99%
“…In this context, reactivation occurs as a two-stage program that overcomes a more compact viral chromatin structure and the absence of tegument factors, such as VP16 (reviewed in Cliffe and Wilson, 2017). During the first stage, termed phase I, there is a transient burst of lytic gene transcription.…”
Section: Loss Of Neurotrophin-associated Signalingmentioning
confidence: 99%